Forest Ornithology (Some Meditations) - Mackenzie, J. M. D. (Indian Forester, 1946)
Forest Ornithology is the very detailed study of our common woodland birds. Nestlings are fed on a diet which is mainly or entirely insects. Mortality is heavy in the first 3 months, so birds eating this beneficial diet preponderate. Provision of nest-boxes is to restore the balance of nature, upset by the removal of old and holey trees. The sequence of birds in plantations is discussed. Certain tree species are preferred to others for nesting by birds which nest off the ground. This can be applied to woods by planting up patches with desirable species. Bats are suggested as a parallel control with birds.